Special fiber material and preparation method thereof

By modifying cellulose and expanded graphite to form a three-dimensional network structure, the problems of reduced mechanical strength and graphite shedding in cellulose-based special fiber materials under humid conditions are solved, and the water resistance and high-temperature flame retardancy of the material are achieved.

CN121065841AActive Publication Date: 2025-12-05BAOJI KEDA SPECIAL PAPER CO LTD

Patent Information

Application Number
CN202511588262.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-03
Publication Date
2025-12-05
Estimated Expiration
2045-11-03

AI Technical Summary

Technical Problem

Existing cellulose-based specialty fiber materials exhibit reduced mechanical strength in humid environments, and expanded graphite is prone to detachment at high temperatures, affecting flame retardant performance.

Method used

By modifying cellulose and expanded graphite, epoxy groups and amino polyethylene glycol silane are introduced to form a three-dimensional network structure, which is then crosslinked with phosphate-based montmorillonite at high temperature to enhance compatibility and stability.

Benefits of technology

It improves the water resistance and mechanical strength of the material, while ensuring that the expanded graphite does not fall off at high temperatures, forming a dense carbonaceous heat insulation layer and enhancing long-term flame retardant performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a special fiber material and a preparation method thereof, and belongs to the technical field of polymer composites.The preparation method comprises the following steps that cellulose and an ethanol solution are mixed, polyvinyl alcohol and a 3-glycidoxypropyltrimethoxysilane solution are added, the pH is adjusted to be acidic, heating, suction filtration and drying are conducted, and modified cellulose is obtained; mixing expanded graphite, deionized water, ammonium persulfate and dilute sulphuric acid, heating, cooling, dropwise adding amino polyethylene glycol silane, heating, washing and drying to obtain modified expanded graphite; the preparation method comprises the following steps: mixing modified cellulose, modified expanded graphite, phosphate montmorillonite, 3-(methacryloyloxy) propyltrimethoxysilane, bisphenol A diglycidyl ether and 2-methylimidazole, stirring, heating, defoaming, and carrying out two-stage constant-temperature treatment to obtain the special fiber material. The special fiber material disclosed by the invention has good flame retardance, mechanical strength, water resistance and filtering performance, and can be applied to various organic composite boards, filter membranes and the like with high quality requirements.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of high polymer composite materials, in particular to a special fiber material and a preparation method thereof. BACKGROUND

[0002] Cellulose is a kind of safe and non-toxic natural polymer material, which is taken from renewable resources such as wood, cotton and straw, and has the advantages of abundant reserves, low price, renewability and environmental friendliness, so it has attracted much attention in the field of green and sustainable materials. With the development of society and the improvement of environmental protection requirements, special fiber materials prepared from cellulose have gradually begun to be applied in the field of flame-retardant boards and filter membrane layers.

[0003] The special fiber material based on cellulose not only has inherent advantages such as light weight and low cost, but also can improve its flame-retardant performance by compounding with functional inorganic fillers, thereby expanding its application in the field of flame-retardant materials. To improve the flame retardancy of the material, a common method is to add inorganic flame-retardant fillers such as expanded graphite to the material system. For example, the patent application file with publication number CN105694505A discloses a surface powdering flame-retardant process for hemp fiber composite material. In this scheme, expanded graphite is added to the hemp fiber composite material by blending, thereby improving the flame retardancy of the hemp fiber composite material to a certain extent. However, the expanded graphite in this scheme does not form effective chemical bonds with the surrounding materials, which leads to the expansion of the material pores when the expanded graphite expands under heat, and the expanded graphite falls off from the pores when it shrinks after cooling, thereby reducing the long-term flame retardancy of the material.

[0004] In addition, the cellulose surface contains a large number of hydroxyl groups, which are highly hydrophilic and easily absorb moisture. In a humid environment, the interaction between fibers is weakened, and as the water content increases, the network structure expands and deforms, resulting in a decrease in the overall mechanical strength of the special fiber material.

[0005] In view of the above, it is necessary to provide a special fiber material and a preparation method thereof to solve the problems existing in the prior art. SUMMARY

[0006] Therefore, the present application provides a special fiber material and a preparation method thereof, which can not only avoid the falling off of expanded graphite to provide good long-term flame retardancy, but also improve the water resistance and mechanical strength of the special fiber material.

[0007] To achieve the above-mentioned purpose, a special fiber material and a preparation method thereof include the following steps: S1, dispersing cellulose in an ethanol solution, stirring, adding polyvinyl alcohol and 3-glycidyloxypropyltrimethoxysilane solution, adjusting the pH of the solution to be acidic, heating and reacting, filtering, washing, vacuum drying, and cooling to obtain modified cellulose; S2, the expanded graphite and deionized water are mixed and stirred, ammonium persulfate and dilute sulfuric acid are added, heated and reacted, cooled, and amino polyethylene glycol silane is added dropwise, heated and stirred, filtered, washed, vacuum dried, and sieved to obtain modified expanded graphite; S3, the modified cellulose and the modified expanded graphite are mixed and stirred, 3-(isobutenoyloxy)propyl trimethoxysilane, bisphenol A diglycidyl ether and 2-methyl imidazole are added, and after being dispersed by heating and shearing, defoaming, pouring into a mold, two-stage constant temperature treatment, cooling to demolding, drying, a special fiber material is prepared.

[0008] The present application modifies the cellulose by 3-glycidyloxypropyl trimethoxysilane, introduces epoxy groups on the surface, and after the hydroxyl groups of the cellulose are replaced, generates siloxane bonds and organosilicon segments, so that the cellulose has persistent hydrophobicity, thereby inhibiting the hygroscopicity of the cellulose in a humid environment. In addition, due to the high surface mineralization degree of the expanded graphite, it is neither hydrophilic nor lipophilic, and it is often difficult to disperse uniformly in the conventional system, and it is easy to have poor compatibility with the cellulose. The present application acidifies the expanded graphite and then treats it with amino polyethylene glycol silane to obtain modified expanded graphite with surface-grafted amino and hydroxyl groups. The epoxy groups of the modified cellulose can undergo ring-opening reaction with the amino and hydroxyl groups on the modified expanded graphite, and under the catalysis of 2-methyl imidazole and two-stage constant temperature treatment conditions, crosslink with 3-(isobutenoyloxy)propyl trimethoxysilane and form a three-dimensional network structure, which not only improves the compatibility and dispersibility of the expanded graphite in the material, but also enhances the overall mechanical strength of the special fiber material.

[0009] In addition, the expanded graphite will expand and contract significantly at high temperatures, and the periodic change in the interlayer volume of the expanded graphite can easily lead to an increase in the pore size of the network structure of the special fiber material, causing the expanded graphite to peel off from the special fiber material, thereby weakening the physical and chemical properties of the special fiber material. In the present application, the expanded graphite is surface-modified by amino polyethylene glycol silane, and the silane end forms a stable Si-O anchor bond on the surface of the expanded graphite, and the amine group can undergo ring-opening reaction with the epoxy group on the surface of the modified cellulose, so that the two are chemically bonded. The PEG segment of the amino polyethylene glycol silane molecule has flexible and reversible stretchability: when the expanded graphite layer expands, the PEG segment contracts moderately to offset the volume change; when the expanded graphite contracts, the PEG segment stretches to fill the interface gap. Through this dynamic adaptation mechanism, the increase in the interface pore is effectively avoided, and the expanded graphite is prevented from peeling off from the fiber material. At the same time, the modified expanded graphite can still expand rapidly when heated, generating a dense carbon heat-insulating layer, which forms a barrier effect to the transfer of heat and oxygen, thereby improving the long-term flame retardant performance of the special fiber material.

[0010] Optionally, in the step S3, the modified cellulose and the modified expanded graphite are mixed and stirred, and a phosphate-based montmorillonite is added, wherein the phosphate-based montmorillonite is obtained by treating montmorillonite with triethyl phosphate.

[0011] In the present application, the montmorillonite is treated with triethyl phosphate to introduce phosphate groups on the lamellar structure of the montmorillonite to obtain the phosphate-based montmorillonite. The phosphate-based montmorillonite no longer exhibits strong hydrophilic properties, but has better compatibility with the modified cellulose, so that it is more easily dispersed in the fiber network to form a uniformly distributed lamellar structure. Meanwhile, under the condition of heat curing, the phosphate groups can undergo ring-opening condensation reaction with the epoxy groups on the surface of the modified cellulose to form phosphate ester bonds and ether cross-linking, thereby constructing an organic-inorganic cross-linking network. The phosphate-based montmorillonite is embedded as a skeleton between the fiber pores, and when the fiber network changes under external force, the interlamellar spacing of the phosphate-based montmorillonite can be offset by slipping or restacking to avoid the collapse of the fiber network and improve the mechanical strength of the material. Meanwhile, the phosphate groups promote the carbonization of the surrounding modified cellulose when heated, and the carbon heat insulation layer barrier formed in cooperation with the modified expanded graphite further improves the flame retardant performance of the material.

[0012] Optionally, the phosphate-based montmorillonite is prepared by mixing the montmorillonite and deionized water, ultrasonic dispersion for 10-15 min, adding anhydrous ethanol, stirring for 10-20 min, adding triethyl phosphate, heating to 50-70℃, stirring for 60-90 min, filtering, washing with anhydrous ethanol and deionized water for 2-3 times, and vacuum drying at 80-90℃ for 1-2 h, and then sieving through a 50-mesh sieve.

[0013] In the present application, the triethyl phosphate is allowed to fully react with the surface of the montmorillonite through ultrasonic dispersion, temperature-controlled reaction and washing to obtain a uniform and stable modification, and the uniformity of the particle size of the phosphate-based montmorillonite is further improved by sieving through a 50-mesh sieve, which is beneficial to its dispersion in the fiber system.

[0014] Optionally, the dried cellulose is mixed and stirred with a 70wt% ethanol solution for 20-25 min, polyvinyl alcohol and a 1wt% 3-glycidyloxypropyltrimethoxysilane solution are added, glacial acetic acid is added dropwise to adjust the pH of the solution to 4-5, and stirring is performed at 50-60℃ for 60-90 min, and then the mixture is filtered, washed with anhydrous ethanol and deionized water for 2-3 times, and vacuum dried at 80-90℃ for 2-3 h. After cooling to room temperature, the modified cellulose is obtained.

[0015] Optionally, the expanded graphite and deionized water are mixed, soaked for 10-15 min, anhydrous ethanol is added, stirred and dispersed for 20-30 min, ammonium persulfate and dilute sulfuric acid are added, stirred at 50-60℃ for 30-60 min, after cooling to room temperature, amino polyethylene glycol silane is slowly added dropwise, stirred at 40-50℃ for 60-90 min, filtered, washed with anhydrous ethanol and deionized water for 2-3 times, vacuum dried at 80-85℃ for 1-2 h, and sieved through a 60-mesh sieve to obtain the modified expanded graphite.

[0016] In the present application, in step S2, ammonium persulfate and dilute sulfuric acid are reacted at 50-60℃ to mildly introduce active sites and avoid damage to the graphite structure, then amino polyethylene glycol silane is added dropwise and reacted under acidic conditions to uniformly bond to the surface of the expanded graphite; the byproducts and solvents are removed through filtration, washing, and vacuum drying; and finally, the modified expanded graphite with uniform particle size is obtained through sieving.

[0017] Optionally, the modified cellulose and the modified expanded graphite are mixed and stirred for 10-20 min, 3-(isobutyryloxy)propyl trimethoxysilane, bisphenol A diglycidyl ether, and 2-methyl imidazole are added, sheared and dispersed at 60-70℃ for 3-5 min, defoamed for 5-8 min, poured into a mold, subjected to two-stage constant temperature treatment, cooled to room temperature, demolded, and dried at 50-60℃ for 1-2 h to obtain the special fiber material.

[0018] Optionally, the two-stage constant temperature treatment is: constant temperature treatment at 90-100℃ for 30-40 min, and heating to 125-130℃ for 1-1.5 h of curing.

[0019] In the present application, pre-reaction is first performed at 90-100℃ to avoid stress concentration caused by sudden crosslinking of the reaction system; and final curing is then completed at 125-130℃ to fully crosslink the fiber network structure, which is conducive to improving the structure compactness and performance stability of the special fiber material.

[0020] A special fiber material includes the following raw materials in parts by weight: modified cellulose 50-60 parts, modified expanded graphite 5-6 parts, 3-(isobutyryloxy)propyl trimethoxysilane 2-5 parts, bisphenol A diglycidyl ether 5-8 parts, and 2-methyl imidazole 0.5-0.8 parts.

[0021] Optionally, the modified cellulose includes the following raw materials in parts by weight: cellulose 50-60 parts, 70wt% ethanol solution 660-750 parts, polyvinyl alcohol 1.5-2.5 parts, and 1wt% 3-glycidyloxypropyl trimethoxysilane solution 10-20 parts. The modified expanded graphite comprises raw materials in the following proportions by weight: expanded graphite 5-6 parts, deionized water 200-250 parts, anhydrous ethanol 620-720 parts, ammonium persulfate 0.6-1 part, 5wt% dilute sulfuric acid 0.2-0.4 parts, and amino polyethylene glycol silane 0.6-1 part.

[0022] Optionally, the special fiber material further comprises phosphate-based montmorillonite, and the phosphate-based montmorillonite comprises raw materials in the following proportions by weight: montmorillonite 1-2.5 parts, deionized water 200-250 parts, anhydrous ethanol 310-400 parts, and triethyl phosphate 0.5-1 part.

[0023] The above technical solutions of the present application at least have the following beneficial effects: The present application modifies cellulose by 3-glycidyloxypropyltrimethoxysilane, introduces epoxy groups on the surface, and replaces the hydroxyl groups of cellulose to form siloxane bonds and organosilicon segments, so that the cellulose has persistent hydrophobicity, thereby inhibiting the hygroscopicity of cellulose. In addition, the expanded graphite is difficult to disperse uniformly in the conventional system due to its high surface mineralization degree, and is prone to poor compatibility with cellulose. The present application acidifies the expanded graphite and then treats it with amino polyethylene glycol silane to obtain modified expanded graphite. The epoxy groups of the modified cellulose can undergo ring-opening reaction with the amino and hydroxyl sites on the modified expanded graphite, and crosslink with 3-(isobutenoyloxy)propyltrimethoxysilane under the catalysis of 2-methylimidazole and two-stage constant temperature treatment conditions to form a three-dimensional network structure, which not only improves the compatibility and dispersibility of the expanded graphite in the material, but also enhances the overall mechanical strength of the special fiber material.

[0024] The expanded graphite will expand and contract significantly at high temperatures, causing the expanded graphite to fall off from the fiber network, thereby weakening the physical and chemical properties of the material. In the present application, the expanded graphite is surface-modified by amino polyethylene glycol silane and then chemically bonded with modified cellulose to improve the stability. The PEG segment of the amino polyethylene glycol silane molecule also has flexible and reversible stretchability, which can dynamically adapt to the expansion and contraction of the expanded graphite and prevent the expanded graphite from falling off from the fiber. At the same time, the modified expanded graphite can still expand rapidly when heated to form a dense carbon heat insulation layer, which forms a barrier to the transfer of heat and oxygen, thereby further improving the flame retardant performance of the material while ensuring the stability of the structure. DETAILED DESCRIPTION

[0025] To make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions of the embodiments of the present application will be described clearly and completely below in combination with the embodiments of the present application. The described embodiments are part of the embodiments of the present application, and all other embodiments obtained by those skilled in the art based on the described embodiments of the present application belong to the scope of protection of the present application.

[0026] Example 1 The 50 g of dry cellulose was dispersed in 660 g of 70 wt% ethanol solution, mechanically stirred for 20 min, 1.5 g of polyvinyl alcohol and 10 g of 1 wt% 3-glycidyloxypropyltrimethoxysilane (KH560) solution were added, and the pH was adjusted to 4 by adding glacial acetic acid dropwise. The reaction was stirred at 50°C for 60 min. The precipitate was collected by suction filtration and washed with anhydrous ethanol and deionized water twice, respectively. After being cooled to room temperature, the modified cellulose was obtained by vacuum drying at 80°C for 2 h.

[0027] The 5 g of expanded graphite was placed in a beaker, pre-wetted with 200 g of deionized water for 10 min, and then 620 g of anhydrous ethanol was added. The mixture was dispersed by magnetic stirring for 20 min, and then 0.6 g of ammonium persulfate and 0.2 g of 5 wt% dilute sulfuric acid were added. The reaction was continuously stirred at 50°C for 30 min. After being cooled to room temperature, 0.6 g of aminopolyethylene glycol silane was slowly added dropwise. After stirring at 40°C for 60 min, the mixture was filtered by suction, washed with anhydrous ethanol and deionized water twice, respectively, and dried at 80°C under vacuum for 1 h. The modified expanded graphite was obtained by sieving through a 60-mesh screen.

[0028] The 1 g of montmorillonite was added to 200 g of deionized water and ultrasonically dispersed for 10 min. Then 310 g of anhydrous ethanol was added and stirred for 10 min. Then 0.5 g of triethyl phosphate (TEP) was added, and the temperature was raised to 50°C. The reaction was stirred for 60 min. The mixture was filtered by suction, washed with anhydrous ethanol and deionized water twice, respectively, and dried at 80°C under vacuum for 1 h. The phosphate ester-based montmorillonite was obtained by sieving through a 50-mesh screen.

[0029] The 50 g of modified cellulose, 5 g of modified expanded graphite, and 1 g of phosphate ester-based montmorillonite were mixed and stirred for 10 min. Then 2 g of 3-(isobutenoyloxy)propyltrimethoxysilane, 5 g of bisphenol A diglycidyl ether, and 0.5 g of 2-methylimidazole were added. After being sheared and dispersed at 60°C for 3 min, the mixture was placed in a vacuum tank and degassed for 5 min. Then the mixture was poured into a mold, and the excess material on the surface of the mold was slowly scraped off to make the surface of the sample flat. The sample was treated at 90°C for 30 min, heated to 125°C for 1 h, and then cooled to room temperature. The sample was demolded and dried at 50°C for 1 h to obtain the special fiber material.

[0030] Example 2 The 55 g of dry cellulose was dispersed in 700 g of 70 wt% ethanol solution, mechanically stirred for 23 min, 2 g of polyvinyl alcohol and 15 g of 1 wt% 3-glycidoxypropyltrimethoxysilane (KH560) solution were added, and the pH was adjusted to 4.5 by adding glacial acetic acid dropwise, and stirred at 55°C for 75 min. The precipitate was collected by suction filtration, washed with anhydrous ethanol and deionized water for 2 times, and dried at 85°C for 2.5 h. After cooling to room temperature, the modified cellulose was obtained.

[0031] The 5.5 g of expanded graphite was placed in a beaker, pre-wetted with 225 g of deionized water for 12 min, and then 680 g of anhydrous ethanol was added. It was dispersed by magnetic stirring for 25 min, and then 0.7 g of ammonium persulfate and 0.3 g of 5 wt% dilute sulfuric acid were added. The reaction was continuously stirred at 55°C for 40 min. After cooling to room temperature, 0.8 g of aminopolyethylene glycol silane was slowly added dropwise. After stirring at 45°C for 70 min, suction filtration was performed, and then washed with anhydrous ethanol and deionized water for 3 times, respectively. Drying was performed at 85°C for 1.5 h under vacuum, and then sieved through a 60 mesh sieve to obtain the modified expanded graphite.

[0032] The 2 g of montmorillonite was added to 230 g of deionized water, ultrasonically dispersed for 12 min, and then 350 g of anhydrous ethanol was added. It was stirred for 16 min, and then 0.8 g of triethyl phosphate (TEP) was added. The temperature was raised to 60°C, and the reaction was stirred for 80 min. After suction filtration, it was washed with anhydrous ethanol and deionized water for 3 times, respectively. Drying was performed at 85°C for 1.5 h under vacuum, and then sieved through a 50 mesh sieve to obtain the phosphate ester-based montmorillonite.

[0033] The 55 g of modified cellulose, 5.5 g of modified expanded graphite, and 1.8 g of phosphate ester-based montmorillonite were mixed and stirred for 15 min. Then 3.5 g of 3-(isobutenoyloxy)propyltrimethoxysilane, 6.5 g of bisphenol A diglycidyl ether, and 0.6 g of 2-methylimidazole were added. After shearing dispersion at 65°C for 4 min, it was placed in a vacuum tank, and degassing was performed for 6 min. Then it was poured into a mold, and the excess material on the mold was slowly scraped off to make the surface of the sample flat. It was treated at 95°C for 35 min, heated to 128°C for 1.2 h for curing, and then cooled to room temperature. After demolding, it was dried at 55°C for 1.5 h to obtain the special fiber material.

[0034] Example 3 The 60 g of dry cellulose was dispersed in 750 g of 70 wt% ethanol solution, mechanically stirred for 25 min, and then 2.5 g of polyvinyl alcohol and 20 g of 1 wt% 3-glycidoxypropyltrimethoxysilane (KH560) solution were added. The pH was adjusted to 5 by adding glacial acetic acid dropwise, and the reaction was stirred at 60°C for 90 min. The precipitate was collected by suction filtration, washed with anhydrous ethanol and deionized water for 3 times, respectively, and dried at 90°C for 3 h under vacuum. After cooling to room temperature, the modified cellulose was obtained.

[0035] Put 6 g of expanded graphite into a beaker, pre-soak with 250 g of deionized water for 15 min, then add 720 g of anhydrous ethanol, disperse under magnetic stirring for 30 min, add 1 g of ammonium persulfate and 0.4 g of 5 wt% dilute sulfuric acid, continue stirring at 60°C for 60 min, cool to room temperature, slowly add 1 g of aminopolyethylene glycol silane, stir at 50°C for 90 min, then filter, wash with anhydrous ethanol and deionized water for 3 times respectively, vacuum dry at 85°C for 2 h, and sieve through a 60 mesh sieve to obtain modified expanded graphite.

[0036] Put 2.5 g of montmorillonite into 250 g of deionized water, ultrasonic dispersion for 15 min, add 400 g of anhydrous ethanol, stir for 20 min, add 1 g of triethyl phosphate (TEP), heat to 70°C, stir for 90 min, filter, wash with anhydrous ethanol and deionized water for 3 times respectively, vacuum dry at 90°C for 2 h, and sieve through a 50 mesh sieve to obtain phosphate ester-based montmorillonite.

[0037] Mix 60 g of modified cellulose, 6 g of modified expanded graphite, and 2.5 g of phosphate ester-based montmorillonite, stir for 20 min, then add 5 g of 3-(isobutenoyloxy)propyl trimethoxysilane, 8 g of bisphenol A diglycidyl ether, and 0.8 g of 2-methyl imidazole, disperse under shearing at 70°C for 5 min, then place in a vacuum tank, deaerate for 8 min, then pour into a mold, slowly scrape off the excess material on the mold to make the surface of the sample flat, heat at 100°C for 40 min, heat to 130°C for 1.5 h, cool to room temperature, demold, and dry at 60°C for 2 h to obtain a special fiber material.

[0038] Example 4 Disperse 50 g of dry cellulose in 660 g of 70 wt% ethanol solution, mechanically stir for 20 min, add 1.5 g of polyvinyl alcohol and 10 g of 1 wt% 3-glycidyloxypropyl trimethoxysilane (KH560) solution, dropwise add glacial acetic acid to adjust the pH to 4, stir at 50°C for 60 min, collect the precipitate by filtration, wash with anhydrous ethanol and deionized water for 2 times respectively, vacuum dry at 80°C for 2 h, cool to room temperature to obtain modified cellulose.

[0039] Put 5 g of expanded graphite into a beaker, pre-soak with 200 g of deionized water for 10 min, then add 620 g of anhydrous ethanol, disperse under magnetic stirring for 20 min, add 0.6 g of ammonium persulfate and 0.2 g of 5 wt% dilute sulfuric acid, continue stirring at 50°C for 30 min, cool to room temperature, slowly add 0.6 g of aminopolyethylene glycol silane, stir at 40°C for 60 min, then filter, wash with anhydrous ethanol and deionized water for 2 times respectively, vacuum dry at 80°C for 1 h, and sieve through a 60 mesh sieve to obtain modified expanded graphite.

[0040] Mix 50 g of modified cellulose and 5 g of modified expanded graphite for 10 min, then add 2 g of 3-(isobutyryloxy)propyl trimethoxysilane, 5 g of bisphenol A diglycidyl ether, and 0.5 g of 2-methyl imidazole, shear and disperse at 60°C for 3 min, then place in a vacuum tank, deaerate for 5 min, then pour into a mold, slowly scrape off the excess material on the mold to make the sample surface flat, treat at 90°C for 30 min, heat to 125°C and cure for 1 h, cool to room temperature, demold, and dry treat at 50°C for 1 h to obtain a special fiber material.

[0041] Example 5 Disperse 55 g of dry cellulose in 700 g of a 70 wt% ethanol solution, mechanically stir for 23 min, add 2 g of polyvinyl alcohol and 15 g of a 1 wt% 3-glycidyloxypropyl trimethoxysilane (KH560) solution, while adding glacial acetic acid to adjust the pH to 4.5, stir and react at 55°C for 75 min, collect the precipitate by suction filtration, wash twice with anhydrous ethanol and deionized water, and vacuum dry at 85°C for 2.5 h, then cool to room temperature to obtain modified cellulose.

[0042] Place 5.5 g of expanded graphite in a beaker, pre-soak with 225 g of deionized water for 12 min, then add 680 g of anhydrous ethanol, magnetically stir and disperse for 25 min, add 0.7 g of ammonium persulfate and 0.3 g of 5 wt% dilute sulfuric acid, continuously stir and react at 55°C for 40 min, cool to room temperature, slowly add 0.8 g of aminopolyethylene glycol silane, stir and react at 45°C for 70 min, then suction filter, wash three times with anhydrous ethanol and deionized water, and vacuum dry at 85°C for 1.5 h, then pass through a 60-mesh sieve to obtain modified expanded graphite.

[0043] Mix 55 g of modified cellulose and 5.5 g of modified expanded graphite for 15 min, then add 3.5 g of 3-(isobutyryloxy)propyl trimethoxysilane, 6.5 g of bisphenol A diglycidyl ether, and 0.6 g of 2-methyl imidazole, shear and disperse at 65°C for 4 min, then place in a vacuum tank, deaerate for 6 min, then pour into a mold, slowly scrape off the excess material on the mold to make the sample surface flat, treat at 95°C for 35 min, heat to 128°C and cure for 1.2 h, cool to room temperature, demold, and dry treat at 55°C for 1.5 h to obtain a special fiber material.

[0044] Example 6 The 60 g of dry cellulose was dispersed in 750 g of 70 wt% ethanol solution, mechanically stirred for 25 min, 2.5 g of polyvinyl alcohol and 20 g of 1 wt% 3-glycidyloxypropyltrimethoxysilane (KH560) solution were added, and ice acetic acid was added dropwise to adjust the pH to 5, and stirred at 60℃ for 90 min. The precipitate was collected by suction filtration, washed with anhydrous ethanol and deionized water for 3 times, and dried at 90℃ for 3 h. After cooling to room temperature, the modified cellulose was obtained.

[0045] The 6 g of expanded graphite was placed in a beaker, pre-wetted with 250 g of deionized water for 15 min, then 720 g of anhydrous ethanol was added, and dispersed under magnetic stirring for 30 min. 1 g of ammonium persulfate and 0.4 g of 5 wt% dilute sulfuric acid were added, and the reaction was continuously stirred at 60℃ for 60 min. After cooling to room temperature, 1 g of aminopolyethylene glycol silane was slowly added dropwise, and the reaction was stirred at 50℃ for 90 min. After suction filtration, the product was washed with anhydrous ethanol and deionized water for 3 times, and dried at 85℃ for 2 h. The modified expanded graphite was obtained by passing through a 60 mesh sieve.

[0046] The 60 g of modified cellulose and 6 g of modified expanded graphite were mixed and stirred for 20 min, then 5 g of 3-(isobutenoyloxy)propyltrimethoxysilane, 8 g of bisphenol A diglycidyl ether and 0.8 g of 2-methylimidazole were added. After shearing dispersion at 70℃ for 5 min, the mixture was placed in a vacuum tank, and defoamed for 8 min. Then the mixture was poured into a mold, and the excess material on the mold was slowly scraped off to make the surface of the sample flat. The sample was treated at 100℃ for 40 min, heated to 130℃ for 1.5 h, and then cooled to room temperature. The sample was demolded and dried at 60℃ for 2 h to obtain the special fiber material.

[0047] The present application also carried out comparative examples and related tests.

[0048] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step S2, no aminopolyethylene glycol silane was added, and the other components and preparation steps were completely consistent. The special fiber material was prepared.

[0049] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in step S1, no 3-glycidyloxypropyltrimethoxysilane was added, and the other components and preparation steps were completely consistent. The special fiber material was prepared.

[0050] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in step S3, no modified expanded graphite was added, and the other components and preparation steps were completely consistent. The special fiber material was prepared.

[0051] The special fiber materials of Examples 1-6 and Comparative Examples 1-3 were respectively prepared into plate materials with a thickness of 5 mm. The water resistance of the plate materials was tested according to the standard GB / T 11718-2021 for the internal bonding strength test after boiling test for moisture resistance performance. The mechanical strength of the plate materials was tested according to the standard GB / T 11718-2021 for static bending strength test. The flame retardancy of the plate materials was tested according to the standard GB / T 18958-2022 for combustion performance test. After the sample was naturally cooled to room temperature, the flame retardancy test was performed again on the sample, and the test was repeated three times. According to the test results of the last time, the combustion performance grade of the sample was recorded, and the test results are shown in Table 1.

[0052] The special fiber materials of Examples 1-6 and Comparative Examples 1-3 were respectively prepared into film materials with a thickness of 0.4 mm. The filtration performance of the film materials was tested according to the standard QB / T 4031-2024 for filtration efficiency test, and the test results are shown in Table 1.

[0053] Table 1

[0054] As can be seen from Table 1, compared with Examples 4-6, phosphonate-based montmorillonite is added in Examples 1-3, which makes the material exhibit better static bending strength and filtration efficiency. The montmorillonite modified by triethyl phosphate can be uniformly dispersed in the three-dimensional network structure and act as a supporting skeleton to resist external force, thereby improving the overall mechanical strength of the special fiber material. At the same time, the introduction of phosphonate-based montmorillonite improves the compactness of the three-dimensional network structure, thereby improving the interception efficiency of the film to particulate matter, and thus improving the filtration performance of the special fiber material.

[0055] Compared with Comparative Example 1, Example 1 introduces amino polyethylene glycol silane, and the PEG segment has flexible and reversible stretchability. When the expanded graphite expands, the segment contracts to offset the volume change. When it cools and contracts, the segment stretches to fill the gap, thereby avoiding the shedding of expanded graphite, and the flame retardancy is better. Comparative Example 1 lacks amino polyethylene glycol silane, and the expanded graphite falls off from the special fiber material due to repeated expansion and contraction, resulting in reduced flame retardancy of the material.

[0056] Compared with Comparative Example 2, Example 1 introduces 3-glycidyloxypropyltrimethoxysilane, which generates a silicon-oxygen bond and an organosilicon segment on the surface of cellulose, forming a stable hydrophobic barrier and reducing water penetration, thereby enhancing water resistance. The cellulose of Comparative Example 2 lacks 3-glycidyloxypropyltrimethoxysilane modification, which makes the material prone to moisture absorption and swelling, thereby reducing the internal bonding strength of the special fiber material after boiling test.

[0057] Compared with Comparative Example 3, Example 1 introduces modified expanded graphite which can expand rapidly at high temperature and form a dense carbon layer to block the transmission of heat and oxygen, thereby improving the flame retardant performance; at the same time, the surface active groups form stable combination with modified cellulose, avoiding the phenomenon of powder falling. Comparative Example 3 lacks modified expanded graphite, and lacks carbon layer protection during combustion, resulting in a decrease in the flame retardant property of the special fiber material.

[0058] The above is the preferred embodiment of the present application, and those skilled in the art can make several improvements and refinements without departing from the principles of the present application, and these improvements and refinements should also be considered within the scope of protection of the present application.

Claims

1. A method for producing a special fiber material, characterized by, The method comprises the following steps: S1, dispersing cellulose in an ethanol solution, stirring, adding polyvinyl alcohol and 3-glycidoxypropyltrimethoxysilane solution, adjusting the pH of the solution to be acidic, heating and reacting, filtering, washing, vacuum drying, cooling, and obtaining modified cellulose; S2, mixing and stirring expanded graphite and deionized water, adding ammonium persulfate and dilute sulfuric acid, heating and reacting, cooling, adding amino polyethylene glycol silane dropwise, heating and stirring, filtering, washing, vacuum drying, sieving, and obtaining modified expanded graphite; S3, mixing and stirring modified cellulose and modified expanded graphite, adding 3-(isobutenoyloxy)propyltrimethoxysilane, bisphenol A diglycidyl ether and 2-methyl imidazole, shearing and dispersing after heating, defoaming, pouring into a mold, cooling to demolding after two-stage constant temperature treatment, and drying to obtain a special fiber material.

2. A method of producing a special fiber material according to claim 1, characterized in that, In the step S3, phosphonate-based montmorillonite is added when mixing and stirring the modified cellulose and the modified expanded graphite, and the phosphonate-based montmorillonite is obtained by treating montmorillonite with triethyl phosphate.

3. A method of producing a special fiber material according to claim 2, characterized in that, The phosphonate-based montmorillonite is prepared by mixing montmorillonite and deionized water, ultrasonic dispersion for 10-15 min, adding anhydrous ethanol, stirring for 10-20 min, adding triethyl phosphate, heating to 50-70℃, stirring and reacting for 60-90 min, filtering, washing with anhydrous ethanol and deionized water for 2-3 times, vacuum drying at 80-90℃ for 1-2 h, and sieving through a 50-mesh sieve.

4. The method for preparing a special fiber material according to claim 1, characterized in that, Mixing and stirring dry cellulose and 70wt% ethanol solution for 20-25 min, adding polyvinyl alcohol and 1wt% 3-glycidoxypropyltrimethoxysilane solution, adjusting the pH of the solution to 4-5 by adding glacial acetic acid dropwise, stirring at 50-60℃ for 60-90 min, filtering, washing with anhydrous ethanol and deionized water for 2-3 times, vacuum drying at 80-90℃ for 2-3 h, and cooling to room temperature to obtain modified cellulose.

5. The method for preparing a special fiber material according to claim 1, characterized in that, Mixing and stirring expanded graphite and deionized water, soaking for 10-15 min, adding anhydrous ethanol, stirring and dispersing for 20-30 min, adding ammonium persulfate and dilute sulfuric acid, stirring at 50-60℃ for 30-60 min, slowly adding amino polyethylene glycol silane after cooling to room temperature, stirring at 40-50℃ for 60-90 min, filtering, washing with anhydrous ethanol and deionized water for 2-3 times, vacuum drying at 80-85℃ for 1-2 h, and sieving through a 60-mesh sieve to obtain modified expanded graphite.

6. The method for preparing a special fiber material according to claim 1, characterized in that, Mixing and stirring modified cellulose and modified expanded graphite for 10-20 min, adding 3-(isobutenoyloxy)propyltrimethoxysilane, bisphenol A diglycidyl ether and 2-methyl imidazole, shearing and dispersing at 60-70℃ for 3-5 min, defoaming for 5-8 min, pouring into a mold, cooling to room temperature after two-stage constant temperature treatment, demolding, and drying at 50-60℃ for 1-2 h to obtain a special fiber material.

7. A method of producing a special fiber material according to claim 6, characterized in that, The two-stage constant temperature treatment is constant temperature treatment at 90-100℃ for 30-40 min, and heating to 125-130℃ for 1-1.5 h of curing.

8. A specialty fiber material made using the method of making a specialty fiber material of claim 1, characterized by, The modified cellulose comprises the following raw materials in parts by weight: cellulose 50-60 parts, 70wt% ethanol solution 660-750 parts, polyvinyl alcohol 1.5-2.5 parts, 1wt% 3-glycidyloxypropyl trimethoxysilane solution 10-20 parts.

9. A specialty fiber material according to claim 8, characterized in that The modified cellulose comprises the following raw materials in parts by weight: cellulose 50-60 parts, 70wt% ethanol solution 660-750 parts, polyvinyl alcohol 1.5-2.5 parts, 1wt% 3-glycidyloxypropyl trimethoxysilane solution 10-20 parts. The modified expanded graphite comprises the following raw materials in parts by weight: expanded graphite 5-6 parts, deionized water 200-250 parts, anhydrous ethanol 620-720 parts, ammonium persulfate 0.6-1 part, 5wt% dilute sulfuric acid 0.2-0.4 parts, amino polyethylene glycol silane 0.6-1 part.

10. A specialty fiber material according to claim 8, characterized in that, The special fiber material further comprises phosphate-based montmorillonite, and the phosphate-based montmorillonite comprises the following raw materials in parts by weight: montmorillonite 1-2.5 parts, deionized water 200-250 parts, anhydrous ethanol 310-400 parts, triethyl phosphate 0.5-1 part.

Citation Information

Patent Citations

  • Formula and preparation technology of light fiber-reinforced thermoplastic resin composite sheet material with high flame resistance

    CN103950251A

  • Surface powder spraying flame-retardant technology for fibrilia composite material

    CN105694505A

  • Preparation method of high-strength high-flame-retardant fireproof coating

    CN111423781A

  • Preparation method of polystyrene thermal insulation material

    CN117430858A

  • Heat-conducting composite film and preparation method thereof, and precursor slurry for manufacturing heat-conducting composite film and preparation method thereof

    CN118496667A

Cited By

  • Multifunctional polyurethane foaming material for building materials and preparation process thereof

    CN121779672A